Centering Our Voices: Experiences of Violence Among Homeless African American Women - Deal, Emily (Violence against women, 2023)
Women experiencing homelessness who are also survivors of violence require uniquely tailored programs to accommodate complex needs. To understand how violence shaped the lives of formerly homeless African American women, an instrumental case study design and community-based participatory research approach was utilized in this qualitative study. Focus group interviews with graduates (N = 40) from a long-term transitional housing program were conducted. Using thematic analysis, identified themes included: cycles of violence, violence in the community, relationships with children, and coping with violence. These themes illustrated survivors’ growth through supportive programming and highlighted services dedicated to empowering women who have experienced violence.